A Look at Local Educational Management in the Context of Decentralization: The Case of Two Municipalities in Peru - Muñoz, Fanni (Education Policy Analysis Archives, 2013)
Through the analysis of two municipalities in northern Peru, this paper examines the operation of local government and the role assigned to education in the context of decentralization. This important State reform process was implemented eleven years ago, and is enabling regional and local governments to encourage decentralized management initiatives in education. This occurs in a global context in which Latin American governments have been promoting various initiatives to improve its quality. It shows how two municipalities from Piura Region (Paita and Morropón) are organized and how they are developing strategies to assume the new competences and responsibilities about education assigned to them by the State reform. With this framework, we analyze the existence of different logics, composition and capabilities in their bureaucracies to take education as a function in specific environments and conditions. The study shows that there are serious difficulties to establish the managerial management model, particularly because there is no qualified bureaucracy. The cases analyzed demonstrate that, although municipalities develop effective actions in education, mainly focused on childhood, education is not a priority of municipal management. These case studies enable us to understand the complexity of the changes in local management in the context of decentralization. The strategies followed provide clues to the implementation of a decentralized educational management.